2020
DOI: 10.3389/fphys.2020.552483
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Aggravates Cholesterol Accumulation in Glomerular Endothelial Cells Through the LXRs/LncRNAOR13C9/ABCA1 Regulatory Network

Abstract: Background: The underlying mechanisms by which diabetes and dyslipidemia contribute to diabetic nephropathy (DN) are not fully understood. In this study, we aimed to investigate the role of high glucose (HG) on intracellular cholesterol accumulation in glomerular endothelial cells (GEnCs) and its potential mechanism. Methods: Oil red O staining, RT-qPCR, Western blotting, and immunocytofluorescence analyses were used to determine cholesterol accumulation and the expressions of LXRs and ABCA1 in GEnCs under hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…At present, domestic and foreign studies have found that a variety of natural active substances have the effect of promoting the outflow of cholesterol from foam cells [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…At present, domestic and foreign studies have found that a variety of natural active substances have the effect of promoting the outflow of cholesterol from foam cells [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…And miR-23a-5p and DYNLRB1 were determined to be involved in various diseases, including renal cell carcinoma, diabetic nephropathy. 17,18 These The results of qRT-PCR displayed that lncRNA (LINCO2532 and SLCO4A1-AS1) and DYNLRB1 were downregulated and the expression of miR23a-5p was upregulated in PE patients compared with healthy controls. Next, the role of miR-23a-5p and DYNLRB1 in PE need to be further investigated in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, leads to the suppression of various signaling pathways and a decrease in pro-inflammatory cytokine levels such as IL-6 and TNF-α. 96,97 However, the clinical application of LXR agonists is hindered by their liver side effects, which result in excessive triglyceride secretion into the systemic circulation. 98 NP-based drug delivery systems offer a promising approach to overcome these challenges.…”
Section: Antibacterial and Antiviral Therapymentioning
confidence: 99%